Design, validation, and reliability of an observational instrument for pivot influence on tactical effectiveness in team-handball - Ávila-Moreno, F.; Lozano-Jarque, D.; Chirosa-Ríos, L. J.; Ortega-Becerra, M. (Kinesiology, 2022)
The objective of this study was to design and study the validity and reliability characteristics of an observational instrument to assess the tactical behavior of pivots in handball and its influence on tactical performance of the team. The process consisted of five stages. In the first two, a combined instrument using field formats and category repertoires was designed. The third stage consisted of validating the content by consulting a panel of highly qualified experts. The fourth phase produced reliability indices, according to Cohen`s Kappa test, for both inter-observer and intra-observer performance, of over .86. Finally, the instrument was applied to a pilot study; a correlational study using Pearson`s Chi-squared test yielded very significant dependence coefficients (p<.001) among variables, confirming the usefulness of the instrument in the search for tactical performance indicators related to the handball pivot.